1994
DOI: 10.1111/j.1475-6811.1994.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and working models of attachment: Consequences for perceptions of self and romantic relationships

Abstract: Several theorists have proposed that differential socialization experiences lead men and women to differ in the importance they assign to relationships and in how they interpret and respond to relationships. To explore this idea, this study examined whether men and women who reported similar attachment experiences responded differently to information about the same kind of relationship. Men and women with secure, preoccupied, or avoidant models of attachment imagined themselves in a relationship with a hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
3
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 43 publications
(49 reference statements)
4
100
3
4
Order By: Relevance
“…In previous research, unusually negative relationship outcomes have been reported for Anxious (Clingy) women and Avoidant (Skittish) men (Collins & Read, 1990;Kirkpatrick & Davis, 1994;Pietromonaco & Carnelley, 1994;Simpson, 1990). Pietromonaco and Carnelley (1994) hypothesized that these unusually high rates of distress and partner unhappiness are due to the fact that the attachment styles of Anxious (Clingy) women and Avoidant (Skittish) men are consistent with traditional gender role socialization: Clingy women's (over)concern with relationships is one cornerstone of traditional female gender role socialization, and Skittish men show the (over)desire for independence that is a major element of traditional male gender role socialization. This consistency of attachment style and socialization may particularly constrain these individuals' behaviors in romantic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, unusually negative relationship outcomes have been reported for Anxious (Clingy) women and Avoidant (Skittish) men (Collins & Read, 1990;Kirkpatrick & Davis, 1994;Pietromonaco & Carnelley, 1994;Simpson, 1990). Pietromonaco and Carnelley (1994) hypothesized that these unusually high rates of distress and partner unhappiness are due to the fact that the attachment styles of Anxious (Clingy) women and Avoidant (Skittish) men are consistent with traditional gender role socialization: Clingy women's (over)concern with relationships is one cornerstone of traditional female gender role socialization, and Skittish men show the (over)desire for independence that is a major element of traditional male gender role socialization. This consistency of attachment style and socialization may particularly constrain these individuals' behaviors in romantic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, people with a more avoidant style report little emotionality (Bartholomew & Horowitz, 1991;Collins & Read, 1990;Hazan & Shaver, 1987;Pietromonaco & Carnelley, 1994;Pietromonaco & Feldman Barrett, 1997). …”
Section: Empirical Foundationsmentioning
confidence: 99%
“…Attachment theory (Hazan & Shaver, 1994) postulates three types of attachment styles: secure, anxious/ambivalent, and anxious/avoidant. Research has shown that individuals prefer partners with an attachment style similar to theirs (Frazier et al, 1996;Pietromonaco & Carnelley, 1994), although recent evidence points to a general preference for securely attached partners (Chappell & Davis, 1998). From a need-based perspective, partner selection satisfies psycho-logical needs, such as the need to belong (Baumeister & Leary, 1995), the need for intimacy (Reis & Shaver, 1988), the need for positive affect maintenance (Sedikides, Oliver, & Campbell, 1994), or the need to expand the self (A. Aron & E. Aron, 1997).…”
Section: Social Psychological Theorizing On Partner Selection: a Briementioning
confidence: 99%